Rekonstruksi Model Murid Mubadir (Inisiator): Analisis Pedagogis Kisah Sulaiman dan Hud-hud (QS. An-Naml: 20-28) - Ahmad Dimyati Ridwan; Cucu Surahman; Elan Sumarna; Zakia Fitri Nabila; Intan Wardatul Karimah (Mu'allim, 2026)
Studies on the concept of the disciple in the Qur'an are often dominated by the "obedient learner model" extracted from the story of Moses and Khidr. Although ethically important, this paradigm is insufficient to address the demands of modern education that emphasize initiative, independence, and critical thinking. This study identifies this pedagogical gap and aims to reconstruct an alternative model to address it. Using qualitative literature study methods and a thematic tafsir approach, this study analyzes in depth the interaction between Prophet Solomon and the Hud-hud (QS. An-Naml [27]: 20-28), enriched with rhetorical analysis (balaghah) and expert views. The results present a prototype of the "Murid Mubadir" (Initiator Disciple), characterized by proactive initiative in seeking knowledge, intellectual courage in reporting findings, systematic analysis, and a sense of responsibility. On the other hand, Prophet Solomon represents the "Wise Teacher" who is open to new information while upholding the principle of verification (tabayyun). This study concludes that the Qur'an offers a polyphonic, not monolithic, concept of the disciple. The story of Hud-hud provides an empowering pedagogical paradigm for Islamic Religious Education (PAI) to shape learners who are not only civilized, but also critical, proactive, and in tune with 21st-century skills.